2008
DOI: 10.1111/j.1095-8649.2008.01973.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of texture on surface attachment of spawning‐run sea lampreys Petromyzon marinus: a quantitative analysis

Abstract: Adult sea lamprey Petromyzon marinus attachment strength by the oral sucker was quantified. Surfaces with shallow, rounded discontinuities into which the oral fimbriae could be folded yielded the strongest seal and some fish could control their mouths to improve 'suction'. Narrow grooves of 1 mm width and 3 mm depth prevented P. marinus from creating a lasting attachment.This study examined the physical characteristics of 'suction' attachment in spawning-run sea lampreys Petromyzon marinus L. Throughout the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…The adhesive performance of pelvic suckers in climbing gobiids was much greater than would have been predicted from the size of the suckers alone, indicating substantial contributions of the fin retractor muscles and potentially other factors to the adhesive performance of these species [e.g. epidermal microstructure or mucus secretion (Arita, 1967;Nachtigall, 1974;Branch and Marsh, 1978;Green, 1979;Emerson and Diehl, 1980;Grenon and Walker, 1981;Green and Barber, 1988;Das and Nag, 2004;Pinky et al, 2004;Cook et al, 1990;Das and Nag, 2005;Goodwyn et al, 2006;Adams and Reinhardt, 2008)]. In addition, the absolute performance of climbing gobiid suckers was high relative to the primary force that set the standard for our comparisons, which was the need to suspend the weight of the body against gravity.…”
Section: Functional Capacity Of the Oral Sucker During Adhesionmentioning
confidence: 99%
“…The adhesive performance of pelvic suckers in climbing gobiids was much greater than would have been predicted from the size of the suckers alone, indicating substantial contributions of the fin retractor muscles and potentially other factors to the adhesive performance of these species [e.g. epidermal microstructure or mucus secretion (Arita, 1967;Nachtigall, 1974;Branch and Marsh, 1978;Green, 1979;Emerson and Diehl, 1980;Grenon and Walker, 1981;Green and Barber, 1988;Das and Nag, 2004;Pinky et al, 2004;Cook et al, 1990;Das and Nag, 2005;Goodwyn et al, 2006;Adams and Reinhardt, 2008)]. In addition, the absolute performance of climbing gobiid suckers was high relative to the primary force that set the standard for our comparisons, which was the need to suspend the weight of the body against gravity.…”
Section: Functional Capacity Of the Oral Sucker During Adhesionmentioning
confidence: 99%
“…Electromyogram studies of free-swimming sea lamprey indicated that they appear to move through arduous passage routes with a saltatory movement pattern, alternately bursting forward, attaching, and resting (Quintella et al 2004(Quintella et al , 2009). In these situations, the cost of attachment is likely increased, as lamprey must expend more energy in the creation of buccal pressure (Adams and Reinhardt 2008). The morphology of the oral disc allows attachment to a variety of surface types with apparently minimal energetic cost (Adams and Reinhardt 2008).…”
Section: Swimming Performance and Energeticsmentioning
confidence: 99%
“…In laboratory studies and in the field, Pacific lamprey demonstrated high motivation and success after repeated ascents of a 1.5-mhigh vertical structure (Kemp et al 2009;Moser et al 2013a). Optimal attachment sites feature regular surfaces made of a slightly rugous material that allows the fimbriae and oral disc to form a tight seal (Adams and Reinhardt 2008). This strategy helps the animals to move through areas of difficult passage (Quintella et al 2004), but can only be utilized if adequate attachment surface on the substrate is available (Keefer et al 2009b).…”
Section: Behavioral Responses To Barriersmentioning
confidence: 99%
“…Where flows are exces-245 sive, however, movements of both species might be hindered by their elongated body morphology and lack of paired fins that reduces their ability of negotiating highvelocity flows when compared to most other migratory fishes (Keefer et al, 2013;Foulds and Lucas, 2013). They 250 demonstrate typical anguilliform swimming under these velocities, referred to as a "burst-and-attach" pattern (Adams and Reinhardt, 2008), which is generally ineffective in high velocity areas such as weir orifices or salmonid fish passes, as these often lack suitable attachment 255 surfaces and/or the water velocity exceeds their critical swimming speeds (Adams and Reinhardt, 2008;Foulds and Lucas, 2013). The ability of P. fluviatilis to utilize fish passage structures on blockages in European rivers was shown 260 by Aronsuu et al (2015), who revealed that all individuals that used a natural-like fish-way (fish pass) were successful in passing the barrier, with individuals showing a strong preference to using this over a technical fish-way.…”
Section: Physical Obstructionsmentioning
confidence: 99%